Pengaruh Budaya Organisasi dan Kompensasi Terhadap Loyalitas Karyawan Dompet Dhuafa - Adrian Adha; Mohamad Fayruz (Peneliti.net, 2022)
This study aims to find out how much influence organizational culture and compensation have on employee loyalty to Dompet Dhuafa. This research was conducted in Dompet Dhuafa. This study used a quantitaf approach. The sampling technique, namely the saturated sampling method in this study, was all employees at Dompet Dhuafa, totaling 74 people (all pupulations were sampled). The data collection technique uses observation in the form of a questionnaire. The data processing techniques carried out by the study are validity tests, reality tests, multiple linear regression tests, coefficients of determination, and simultaneous tests. Organizational Culture Variables (X1), Compensation (X2) and Loyalty (Y) validity test results have a CITC value greater than 0.3. The result of the study was a significant level of Pvalue (0.000) < 0.05 which means that there is an influence between Organizational Culture and loyalty, which is 61.8%. Meanwhile, Compensation to Loyalty also had an effect of 29.3%, which means that there is an influence between Organizational Culture and Compensation on loyalty, which is 62.1% while the remaining 37.9% is influenced by other variables that were not studied in this study